The concise dictionary of pastoral care and counseling - Asquith, Glenn H. (Nashville Abingdon Press, 2010)
The Concise Dictionary of Pastoral Care and Counseling is a condensed versionof the Dictionary of Pastoral Care and Counseling, first published in 1990, with new and updated articles. This book provides classic and key articles that explain current theories, trends, and practices in the field of Pastoral Care and Counseling. Contents include: Definitions; History and Biography; Issues of Power and Difference; Interfaith Issues and Methods; Clinical Method; and Pastoral Theological Method.